Risk factors and clinical outcomes of encapsulating peritoneal sclerosis: A case–control study from China - Lu, Miaoqing; Ye, Hongjian; Chen, Dongni; Yi, Chunyan; Lin, Jianxiong; Mao, Haiping; Yang, Xiao; Yu, Xueqing; Chen, Wei (Peritoneal dialysis international, 2022)
Background: Encapsulating peritoneal sclerosis (EPS) is an uncommon, but serious complication in patients with continuous ambulatory peritoneal dialysis (PD) who have a considerable mortality rate. This study aimed to identify risk factors and outcomes of EPS in Chinese patients on PD. Methods: Sixteen patients on PD who met the International Society for Peritoneal Dialysis criteria for diagnosis of EPS in the First Affiliated Hospital of Sun Yat-Sen University from 1997 to 2018 were included. Patients without EPS were matched for age, sex and the duration of PD and selected at a 1:3 ratio for the controls. A case–control study was conducted to analyse the clinical profile and risk factors associated with EPS in patients. Results: The prevalence of EPS in patients on PD in our centre was 0.55%. The percentage of EPS significantly increased with the duration of PD. In univariate regression analysis, a history of peritonitis (odds ratios (OR): 2.83; 95% confidence interval (CI): 0.82–9.68; p = 0.08), peritoneal glucose exposure (OR: 1.12; 95% CI: 1.03–1.22; p < 0.01) and a high peritoneal transport status (OR: 14.70; 95% CI: 1.85–117.02; p < 0.01) were associated with EPS in patients on PD. However in the multivariate model, only a high peritoneal transport status (adjusted odds ratios (aOR): 13.65; 95% CI: 1.69–109.96; p = 0.01) was independently associated with EPS. Conclusion: The rate of EPS significantly increases with the duration of PD. Progressive peritoneal dysfunction, especially a high peritoneal transport status, is associated with a higher risk of EPS in this population.